Tetraquarks at large M and large N - Héloïse Allaman; Majid Ekhterachian; Filippo Nardi; Riccardo Rattazzi; Stefan Stelzl (Journal of High Energy Physics)
Abstract We study tetraquarks in large N QCD with heavy quarks, in the domain where non-relativistic quantum mechanics offers an adequate approximation. Within the regime of validity of the Born-Oppenheimer approximation, we systematically study and explicitly construct tetraquark states. At leading order in the 1/N expansion, the bound spectrum consists of free mesons, while the 1/N corrections give rise to a Born-Oppenheimer potential that can bind the mesons into tetraquarks. We find two different types of tetraquarks, each endowed with distinct color-spatial wavefunctions. These states arise in the presence of an O $$ \mathcal{O} $$ (N) mass hierarchy between the quarks and the antiquarks. We provide a quantitative argument indicating that only for such a hierarchy is the ground state of the system a tetraquark. We discuss what the extrapolation of our results to realistic values of the parameters may imply for the QCD tetraquark states.